2021
DOI: 10.3390/su13158325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Critical Limit of Sulphur in Soils for Wheat (Triticum aestivum L.) and Mustard (Brassica napus L.)

Abstract: The conception of critical limit (CL) of a nutrient element distinguishes its deficiency from sufficiency, which could advise fertilizer application. A pot culture experiment was conducted during Rabi season (2019–2020) to study the CL of sulphur (S) in soil and plant. A total of 20 soil samples collected from intensive cropping areas of three agroecological zones (AEZs) of Bangladesh were used in the experiment. The 0.15% CaCl2 extractable S (expressed as available S) contents of the test soils ranged from 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Isolation of the threshold value of available Mn in the soil can be performed by taking into account the maximum R 2 value with the corresponding presumed CL for soybean, which can be pointed out at 3.55 µg g −1 . According to some previous reports, the graphical method for estimating CL gives a higher value compared to the statistical method [46]. Either of the methods (graphical or statistical) can be utilized to ascertain the CL of nutrients in the soil, as the values of CL determined using two different methods are very close.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of the threshold value of available Mn in the soil can be performed by taking into account the maximum R 2 value with the corresponding presumed CL for soybean, which can be pointed out at 3.55 µg g −1 . According to some previous reports, the graphical method for estimating CL gives a higher value compared to the statistical method [46]. Either of the methods (graphical or statistical) can be utilized to ascertain the CL of nutrients in the soil, as the values of CL determined using two different methods are very close.…”
Section: Discussionmentioning
confidence: 99%
“…However, this dispute requires further investigation to know why the CL is lower in the statistical method than the graphical method. It was already reported that the statistical approach for determining CL provides a lower value than the graphical approach [28]. Researchers can use any method to determine the CL of nutrients in the soil because the CL values are similar in both methods.…”
Section: Discussionmentioning
confidence: 99%
“…A competent approach should be able to forecast the amount of plant-available nutrients and the fertilizer responsiveness of crops grown in a variety of soils. In this regard, determining CL via two different methodologies is imperative in determining the optimum fertilizer demand [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Land 2023, 12, 1160 2 of 20 the intensification of agriculture coupled with the use of high yielding varieties [5] further aggravated the deficiency depleting the soil reserve. Such deficiency caused significant yield reduction in different cropping systems, and it was up to 50% in cereals [6] while the optimum supply of S could enhance the nutritional quality and yield [7]. Deficiency of S could also lower the utilization efficiency of N and deteriorates the crop quality [8].…”
Section: Introductionmentioning
confidence: 99%